Language and politics - Joseph, John Earl (Edinburgh textbooks in applied linguistics., 2006)
Language, this book argues, is political from top to bottom, whether considered at the level of an individual speaker's choice of language or style of discourse with others (where interpersonal politics are performed), or at the level of political rhetoric, or indeed all the way up to the formation of national languages. By bringing together this set of topics and highlighting how they are interrelated, the book will function well as a textbook on any applied or sociolinguistic course in which some or all of these various aspects of the politics of language are covered. The chapter headings include: How politics permeates language (and vice-versa) Language and nation The social politics of language choice and linguistic correctness Politics embedded in language Taboo language and its restriction Rhetoric, propaganda and interpretation Power, hegemony and choices